Adolescent Knowledge About the Dangers of Free Sex - Fitriani Fitriani; Ridni Husnah; Ichi Salsabila (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Counseling is a way of spreading messages about reproductive health in this case sex education which is an important message about the dangers of sex. Objectives: The purpose of this study was to determine the effect of counseling on the dangers of free sex on the knowledge of adolescents in Mts Darul Falah Batam District in 2021. Methods: The research method is a quantitative study using the Quasy Experiment method with a "one group pre-test and post" approach. test design", in this design there are from before counseling and after counseling. at the final measurement (Post-Test) get a value of p = 0.00 or p <0.05, meaning that there is a difference in the level of knowledge of the dangers of free sex in the final measurement. Results: The research method is a quantitative study using the Quasy Experiment method with a "one group pre-test and post" approach. test design", in this design there are from before counseling and after counseling. at the final measurement (Post-Test) get a value of p = 0.00 or p <0.05, meaning that there is a difference in the level of knowledge of the dangers of free sex in the final measurement. Conclusion: There is an effect of counseling about sexuality on the knowledge of the dangers of free sex in early adolescents.